The Ban of Trade between New Spain and Peru: genesis of a real cédula throughout the historic conjunction of the Spanish Monarchy - De la Serna Nasser, Bruno (2020)
This paper discusses, from a transnational point of view, the historical context that led Philip IV to decree a total prohibition of trade between the viceroyalties of New Spain and Peru in 1634. It revisits the discussion among diverse figures and institutions across the Empire, taking into consideration the complex domestic and international developments in the previous years; and, in this light, ponders to what extent Imperial Spain was a polycentric monarchy.